Estimation of inelastic displacement ratios for soil-structure systems with embedded foundation considering kinematic and inertial interaction effects. (15th March 2018) - Bararnia, Majid; Hassani, Nemat; Ganjavi, Behnoud; Ghodrati Amiri, Gholamreza
Highlights: Effects of SSI on embedment foundation systems are parametrically investigated. Over 7326 SSI systems with embedment foundation under 19 earthquakes are analyzed. Effects of both kinematic and inertial interaction are considered. A simplified expression for estimating Cr of SSI systems is proposed. Abstract: In this research, the simultaneous effects of soil-structure interaction (SSI) and nonlinear behavior of the superstructure on inelastic displacement ratios of soil-structure systems with embedded foundation are parametrically investigated. Results involving both kinematic interaction (KI), including rocking foundation input motion (RFIM), and inertial interaction effects are considered and discussed. The effect of KI on the inelastic displacement ratios is investigated with special focus on the role of rocking foundation input motion. The soil-structure system is modeled by sub-structure method. The foundation is modeled as a rigid cylinder embedded in the soil with different embedment ratios. A large number of soil-structure systems with embedded foundation having various dynamics characteristics and SSI key interacting parameters have been analyzed under an ensemble of 19 earthquake ground motions recorded on alluvium deposits. Results reveal that using the inelastic displacement ratios of fixed-base systems leads to an underestimation of the peak inelastic demands for soil-structure systems. The phenomenon is less intensified as foundation embedment increases. Moreover, the effects of rocking foundation input motion due to KI on inelastic displacement demands are significant for deeply embedded foundation when the SSI effect is predominant. For practical purpose, a simplified expression for estimating inelastic displacement ratios of soil-structure systems with embedded foundation considering KI effects is proposed.